(3EOGQI GdCYeGd GdGSJQGJjLjI s - (3eOGM YQGjHj(B, (3GdMGLs ((3GdLRGFQ(B:s (3OjhGf GdeWHhYGJ GdLGeYjI(B,s, 2015)
(3JfGhd gPG GdcJGH EOGQI GdCYeGd GdGSJQGJjLjI, MjK JMOK ef NdGd aUhd OQGSJg Yf GdeDSSI hYdGbJgG HGdeMjW hYf GdJNWjW , GdGSJQGJjLjI heOGQS GdJacjQ GdGSJQGJjLj hNWhGJ hSjQhQI UjGZI ESJQGJjLjI GdeDSSI, HGdGVGaI Gdi GdQDjI GdGSJQGJjLjI heLGd fTGW GdeDSSI , hGdJTNjU GdNGQLj hGdOGNdj ddeDSSI , cPdc GdNjGQGJ GdGSJQGJjLjI hELQGAGJ hNWhGJ JfajPgG(B.s
(3GdeQGLY U(B.319s
Keywords: (3EOGQI GdCYeGds; (3GdESJQGJjLjIs